The Role of Exosomal microRNA in Cancer Drug Resistance - Guo, Qiao-ru; Wang, Hui; Yan, Ying-da; Liu, Yun; Su, Chao-yue; Chen, Hu-biao; Yan, Yan-yan; Adhikari, Rameshwar; Wu, Qiang; Zhang, Jian-ye (Frontiers in Oncology, 2020)
Exosomes affect the initiation and progression of cancers. In the tumor microenvironment, not only cancer cells, but also fibroblasts and immunocytes secrete exosomes. Exosomes act as a communicator between cells by transferring different cargos and microRNAs (miRNAs). Drug resistance is one of the critical factors affecting therapeutic effect in the course of cancer treatment. The currently known mechanisms of drug resistance include drug efflux, alterations in drug metabolism, DNA damage repair, alterations of energy programming, cancer stem cells and epigenetic changes. Many studies have shown that miRNA carried by exosomes is closely associated with the development of drug resistance mediated by the above-mentioned mechanisms. This review article will discuss how exosomal miRNAs regulate the drug resistance.